X Chromosome Inactivation Timing is Not eXACT: Implications for Autism Spectrum Disorders - LaSalle, Janine M. (Frontiers in Genetics, 2022)
The etiology of autism spectrum disorders (ASD) is complex, involving different combinations of genetic and environmental factors. My lab’s approach has been to investigate DNA methylation as a tractable genome-wide modification at the interface of these complex interactions, reflecting past and future events in the molecular pathogenesis of ASD. Since X-linked genes were enriched in DNA methylation differences discovered from cord blood from newborns later diagnosed with ASD, this has prompted me to review and revisit the recent advancements in the field of X chromosome inactivation (XCI), particularly in humans and other primates. In this Perspective, I compare XCI mechanisms in different mammalian species, including the finding of the noncoding transcript XACT associated with X chromosome erosion in human pluripotent stem cells and recent findings from non-human primate post-implantation embryos. I focus on the experimentally challenging peri- and post-implantation stages of human development when the timing of XCI is prolonged and imprecise in humans. Collectively, this research has raised some important unanswered questions involving biased sex ratios in human births and the male bias in the incidence of ASD.